(3GdCMGOjK GdCQHYhf GdeJHGjfI GdCSGfjO hGdeJhfs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3GdeOjfI GdYRjRjI HLhGQ LGeY Hfi CejI HOeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HGjf Hjf YHGOg CeG HYO aEf GdCMGOjK GdfHhjI hGdCKGQ GdeMeOjI CUd GdYdhe HYO GdbQBf s
(3BNQgG (B:s
(3aYdjg ef QHi GJe UdGJg hcPGc ef WjH GdSdGe GdCced bGd GdeDda GHbGAg Gddg JYGdi (B: (3BNQ GdcJGH GdPi ajg GdCMGOjK GdCQHYhf GdeJHGjfI GdCSGfjO hGdeJhf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW CMjGfkGs
(3Ydi MhGTjgG SeGY ef fGSNgG Ydi GdeDda hHBNQgG SeGY (B836 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs